Spatiotemporal Analysis of Nodding Syndrome in Northern Uganda 1990-2014 - Ongaya, Kizito; Aturinde, Augustus; Farnaghi, Mahdi; Mansourian, Ali; Maiga, Gilbert; Oyo, Benedict; Bagarukayo, Emily (Scientific Research Publishing, 2020)
The emergence of nodding syndrome (NS) in Northern Uganda has generated controversial views with respect to patterns, natural history, and aetiology of the disease which is yet unknown. This study explored spatial patterns of NS using spatial-temporal methods to establish its clustering patterns across both space and time. Village and year of NS onset for individual patients between the years 1990 and 2014 were entered as input for spatial and temporal analysis in the 6 districts in northern Uganda where it is prevalent. Our temporal results showed that NS onset started before the population was moved in Internally Displaced People’s (IDPs) camps. It also shows that NS continued to be reported during the IDPs and after people had left the IDPs. Our spatial and spatiotemporal analysis showed that two periods had persistent NS clusters. These were 2000-2004 and 2010-2014, coinciding with the period when the population was in the IDP camps and when the population was already out of the camps, respectively. Our conclusion is that the view of associating NS outbreak with living conditions in IDP camps is thus coincidental. We, therefore, contend that the actual aetiological factor of NS is still at large.
Keywords: Nodding Syndrome; Spatiotemporal; Spatial Analysis; Northern Uganda